2015
DOI: 10.1038/nrn4038
|View full text |Cite
|
Sign up to set email alerts
|

A fronto–striato–subthalamic–pallidal network for goal-directed and habitual inhibition

Abstract: Classically, the basal ganglia have been considered to have a role in producing habitual and goal-directed behaviours. In this article, we review recent evidence that expands this role, indicating that the basal ganglia are also involved in neural and behavioural inhibition in the motor and non-motor domains. We then distinguish between goal-directed and habitual (also known as automatic) inhibition mediated by fronto-striato-subthalamic-pallido-thalamo-cortical networks. We also suggest that imbalance between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
471
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 482 publications
(498 citation statements)
references
References 187 publications
23
471
0
4
Order By: Relevance
“…These results are comparable to those obtained in previously task related fMRI (Jahanshahi et al 2015) and rs-fMRI connectivity studies (Fig. 3).…”
supporting
confidence: 92%
“…These results are comparable to those obtained in previously task related fMRI (Jahanshahi et al 2015) and rs-fMRI connectivity studies (Fig. 3).…”
supporting
confidence: 92%
“…The loops are anatomically and functionally segregated, and relevant for specific domains of complex human communication [18-20]. The limbic loop includes, but is not limited to, the hippocampus and amygdala (dark blue, left panel of Fig.…”
Section: Outline Of Synopsismentioning
confidence: 99%
“…From a review of several strands of evidence from animal, imaging, clinical studies and behavioural and electrophysiological investigations of the impact of surgery on movement disorders, it has been suggested that the fronto-striato-subthalamic-pallidal networks mediate goal-directed (volitional, effortful inhibition to achieve a goal) and habitual (automatic) inhibition in the motor and non-motor domains [1]. The stop signal task [2] has been extensively employed for assessment of inhibition of ongoing motor responses.…”
Section: Introductionmentioning
confidence: 99%